Strategi Komunikasi Pemasaran Event PERSIS E-Sports - Trisdiyati, Almas Milenita Salsa; Sari, Ratna Permata (Jurnal Mahasiswa Komunikasi Cantrik, 2024)
E-sports is a rapidly growing new branch of sport in Indonesia and worldwide. In Indonesia, E-Sport has gained recognition from IeSPA (Indonesia e-Sport Association), which operates under the Ministry of Youth and Sports. IeSPA's vision is to establish Indonesia as a high-achieving country in the field of E-Sport. As E-Sport continues to develop in Indonesia, numerous competitions have emerged in this domain. It started with small-scale competitions in internet cafes, gradually expanding to both local and international levels. One notable example is the Esports team, PERSIS Esports, which originated from the PERSIS Solo football club in Indonesia. Compared to other League 1 promotion clubs like Dewa United and Rans Nusantara, PERSIS Esports actively organizes Esports events, as evident from their Instagram account. These sporting competitions run successfully due to PERSIS E-Sports' marketing efforts, particularly in Free Fire and E-Football competitions. Data for this research was collected through interviews with the General Manager of PERSIS ESPORTS, Creative Director, Content Creator, and Community Manager. After analysis, the research findings indicate that PERSIS E-Sports effectively markets E-Sports competitions to the target audience, specifically focusing on the 13-18 age range of students in the Solo Raya region who have an interest in online gaming. The marketing strategy involves targeting Instagram users and communities interested in online gaming through Instagram ads. The positioning of Persis E-Sports is to market tournaments that cater to all groups, particularly online gaming communities in Surakarta and its surrounding areas. The implementation of the marketing mix elements (7P) can be observed through the utilization of print media, electronic media, social media, websites, direct marketing via WhatsApp Groups with the community, as well as personal sales activities through booths and expos during events and promotions at local schools in collaboration with their football team.